(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
This article explores the manner in which the underdevelopment of Zimbabwean Sign Language (ZSL) has prevented ZSL from developing into an equally developed language in Zimbabwe. The investigation is grounded on Zimbabwe’s lack of ZSL in postsecondary and higher education, along with the absence of foreign sign languages like American, British, or French, leading to marginalization and hindering the deaf community’s full potential. The study utilized document analysis, focus group discussions with deaf vendors in Harare, Zimbabwe’s Market Square and Copa Cabana bus termini, and semi-structured interviews with executive directors of organisations for the Deaf. The chapter highlights the negative impact of nonstandard sign language in Zimbabwe, highlighting the lack of foreign sign language teaching and standardized sign language on the Deaf community’s participation in national development issues. Despite Zimbabwe’s Constitution recognizing 16 official languages, including ZSL, deaf individuals still face prejudice and discrimination. Inclusive education forces signers to adopt spoken languages, while schools often deny deaf students, hindering their future contributions. The lack of international sign language training also makes it difficult for Deaf individuals to find jobs abroad and transfer money home.